Art as a phenomenon of the culture - O.I. Shramko (Academy of Cognitive and Natural Sciences, 2009)
In ihe article examined циехіюпз of ihf зепсе of the art ax the phenomenon of the essence of the culture, outlined interrelation and relationship of the art and the culture.